SISTEM INFORMASI AKTIVITAS PEGAWAI TERPADU UNIVERSITAS SAHID SURAKARTA - Riskyanto Pangemanan; sri huning Anwariningsih; Dahlan Susilo (JURNAL GAUNG INFORMATIKA, 2013)
The role of information is increasingly needed to support an activity. In line with the development of information technology both hardware and software is rapidlyincreasing, then it should be an institution can take advantage of advances in information technology. One form of utilization is for the development of informationsystems that can support the activities of employees in making a decision. With this system, the activity of employees in an institution can be optimally and efficiently so asto increase productivity. Integrated Activity Information Systems Employee of Sahid Surakarta University is a software for data processing activities of employees andlecturer university Sahid Surakarta. Functions that any activities at the University of Sahid Surakarta both outside and inside the campus can be controlled so as to minimizeconflict of schedule.